Analysis of Standard Process Implementation on Micro Teaching of Mathematics Education Students - Nurdiansyah, Rikrik; Turmudi, Turmudi; Jupri, Al (Unnes Journal of Mathematics Education, 2017)
The purpose of this research was to determine implementing process standard, on planning and implementing which arranged and conducted by math education students. This research method was qualitative study. The research subject consisted of 37 students. The instruments were analysis of lesson plan and learning activity. The analysis technique used data collection, data reduction, data presentation and data verification. The result showed that : 1) overall lesson plan arranged by students has implemented standard process; 2) implementation of learning mathematics has been done by students was lack of implementing standard process. Particularly on student motivating aspect, implementation of learning method, utilization of learning media, management of student centered classroom and the role of teacher was more a source of learning and as an advisor than as a facilitator and motivator; 3) the compatibility level between lesson plan and learning activity were at low level.